Assessment of FGPM shunt damping for vibration reduction of laminated composite beams. (17th February 2017) - Lezgy-Nazargah, M.; Divandar, S.M.; Vidal, P.; Polit, O.
Abstract: This work addresses theoretical and finite element investigations of functionally graded piezoelectric materials (FGPMs) for shunted passive vibration damping of laminated composite beams. The properties of piezoelectric patches are assumed to vary through the thickness direction following the exponent or power law distribution in terms of the volume fractions of the constituent materials. By employing Hamilton's principle, the governing differential equations of motion are derived. The resulting system of equations of vibration is solved by employing an efficient three-nodded beam element which is based on a refined sinus piezoelectric model. The effects of effective electromechanical coupling coefficients (EEMCCs), different electric shunt circuits and different material compositions on the shunted damping performance are investigated. The optimal values of the electric components belonging to each shunt circuit are numerically determined. Highlights: Application of FGPMs for shunted passive vibration damping of laminated composite beams is investigated. Application of FGPM transducers for shunted damping increases the reliability of the passive control networks. For shunted damping of vibrations in practical conditions, R-LIIC shunt circuit is the best suitable choice. The damping performance of different shunt circuits increases drastically with the increasing of the material gradient composition of FGPM transducers.